[PP.07.21] PARG GENE POLYMORPHISM IS ASSOCIATED THE DEVELOPMENT OF LEFT VENTRICULAR HYPERTROPHY IN ARTERIAL HYPERTENSION. (September 2016) - Minushkina, L.; Nikitin, A.; Brazhnik, V.; Nosikov, V.; Zateyshchikov, D.
Abstract : Objective: The purpose of the study was to investigate a possible association of polymorphic markers of the gene encoding nuclear receptor of PPAR family and nuclear proteins PARP and PARG, elements of the antioxidant defense system and endothelial NO-synthase with the development of target organs lesions in hypertension. Design and method: Study population consists of 212 AH patients (pts). The lack of consent to participate, prior myocardial infarction and valvular heart disease were exclusion criteria. There were 94 (44.3 %) men and 118 (55.7 %) women. The mean age of the pts was 60.23 ± 0.74 years, duration of hypertension was 14, 2 ± 0, 79 years. We found LVH in 127 of 212 pts. LVH pts were older than those without LVH, there were more women than men among them, had a longer arterial hypertension case history and had higher values of maximum systolic blood pressure. Results: Association of alleles and genotypes frequencies of PPARG2, PPARG3, PPARA, PPARGC1A, PARP1, ADPRT1 genes and LVH were not found LVH was associated with a higher frequency of 4a allele of NOS3 gene (OR 1, 68 CI [1, 07–2.62], p = 0, 016) and lower frequency of 4b/4b genotype (OR 0, 43 [0, 23–0, 79], p = 0, 005) and 4b allele (OR0, 59 [0, 37–0, 93], p = 0, 016). Also LVH was associated with a higher frequency of GG genotype (OR 3, 61 CI [1, 21–12, 91], p = 0, 024) and G allele (OR = 1, 64 CI [1, 01–2, 67], p = 0, 03) and a lower frequency of A allele (OR 0, 27 CI [0, 07–0, 98] p = 0, 03) of PARG gene. Carriers of rare GG genotype (A (−431) G of PARG) had a significantly greater LVMM and LVMI compared to carriers of the A allele. Carriers of CC genotype (C24313G) of PPARA gene had statistically significant thicker walls of left ventricular, more LVMM and LVMI and no differences in left ventricular function parameters. Carriers of 4a allele of NOS3 gene had significantly greater thickness of the wall of left ventricular and significantly higher LVMI. Conclusions: Age, systolic blood pressure, polymorphism of NOS3 and PARG genes were independently associated with LVH in multivariate regression analysis.